Relevansi Pendidikan Islam Berbasis Melayu di Era Media Sosial: Integrasi Adab dan Teknologi : Penelitian - Putri, Ismarani Junia; Annur, Saipul; Niswah, Choirun (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Malay Islamic education has a long-standing tradition in shaping character, morality, and cultural identity through the cultivation of adab, courtesy, and respect for teachers. However, the development of social media presents new challenges, including the degradation of communication ethics, uncontrolled information flow, and the weakening of scholarly authority. This study aims to analyze the relevance of Malay-based Islamic education in the digital era and to explore how the integration of adab and technology can be applied in modern educational practices. Using a qualitative method through library research, this study examines classical and contemporary literature related to Malay Islamic education, adab, digital culture, and technological literacy. The findings indicate that the value of adab plays a strategic role as a moral, social, and epistemological filter in the use of technology among younger generations. The integration of ta’dib, ethical digital literacy, and the habituation of polite communication are key to preserving the dignity of Malay culture in digital spaces. This article concludes that the success of Malay Islamic education in the social media era depends largely on the ability of educational institutions, teachers, and families to harmoniously combine traditional values with technological competence, thereby producing a generation that is digitally skilled and morally grounded.